2020
DOI: 10.3390/en13051057
|View full text |Cite
|
Sign up to set email alerts
|

What Influences Chinese Consumers’ Adoption of Battery Electric Vehicles? A Preliminary Study Based on Factor Analysis

Abstract: The rapid development of automobile industry in China did improve people’s quality of life. However, it has also damaged the ecological environment. The emission of a large amount of automobiles is one of the serious air pollution sources. In recent years, the shortage of petrochemical energy, the rapid rise of harmful particles in the air (e.g., PM2.5 and PM10), and the increasing worse atmospheric environment are becoming obstacles to China’s sustainable development. Battery electric vehicles (BEVs) are reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…A total of 356 questionnaires were collected, with invalid questionnaires such as those with a short answer time, duplicate answers filled in, missing answers and so on being deleted, and 328 valid questionnaires were left. There was a response rate of 92 percent for the surveys, and the sample size was sufficient for the factor analysis [65][66][67][68][69]. In total, 31.5 percent of the responders were men, while 68.5 percent of them were women.…”
Section: Participantmentioning
confidence: 99%
“…A total of 356 questionnaires were collected, with invalid questionnaires such as those with a short answer time, duplicate answers filled in, missing answers and so on being deleted, and 328 valid questionnaires were left. There was a response rate of 92 percent for the surveys, and the sample size was sufficient for the factor analysis [65][66][67][68][69]. In total, 31.5 percent of the responders were men, while 68.5 percent of them were women.…”
Section: Participantmentioning
confidence: 99%
“…Dos Santos et al (2021), through the artificial neural network (ANN) model, discovered that the higher the purchase price of an internal combustion engine (ICE) vehicle, the higher probability that the consumers will opt for an electric vehicle (EV) instead. The findings of Wei et al (2020) revealed that the preference of purchasing a vehicle differs between drivers and nondrivers of the selected vehicle. Respondents who own and drive electric cars believe that purchasing cost is the main factor when buying a vehicle rather than the one who is not.…”
Section: Financial Attributesmentioning
confidence: 99%
“…Therefore, the various sources of use restriction (e.g., small fuel tank, driving range and charging point's availability) are important to explore as they potentially affect consumers' preferences. Wei et al (2020) examined the vehicles' characteristics based on demographic analysis and discovered that gender factor significantly differentiates the choice of BEV design and battery capacity. Unlike other car owners, the ones who own BEV agreed that attributes of the vehicles significantly affect their purchasing behavior.…”
Section: The Technical Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to rapid economic development and urbanization, China has become the largest automobile market in the world, with an average growth rate of 17.5% since 2000 [1]. The rapid development of China's automobile industry has indeed improved people's quality of life, but it has also destroyed the ecological environment [2]. In 1990, there were only 800,000 private cars in China, while in 2007, the total number of private cars reached 28.8 million and the stock of private cars increased by about 36-fold [3].…”
Section: Introductionmentioning
confidence: 99%